2015
DOI: 10.1080/14786419.2015.1095744
|View full text |Cite
|
Sign up to set email alerts
|

Antioedematogenic activity, acetylcholinesterase inhibition and antimicrobial properties of Jacaranda oxyphylla

Abstract: Jacaranda oxyphylla Cham. (Bignoniaceae) is a shrub found in the Brazilian cerrado and used in folk medicine to treat microbial infections. The aim of this study was to carry out a phytochemical screening and evaluate antioedematogenic, antimicrobial and antiacetylcholinesterase properties of J. oxyphylla crude extracts. All extracts analysed showed presence of terpenoids, which are potentially active chemical substances. A high AChE inhibitory activity for hexane extract from leaves and for the extracts from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
1
2
0
2
Order By: Relevance
“…The component presented potent AChE inhibition activity where the result was further confirmed by docking analysis. This is in agreement with a recent study (Pereira et al, 2016) describing AChE activity of β-sitosterol which was better than oleanolic acid, ursolic acid, and corosolic acid. On the other hand, ethanol extracts of S. multicaulis exhibited a high level of inhibitory activity against BChE in contrast to AChE.…”
Section: Neuroprotectivesupporting
confidence: 93%
See 1 more Smart Citation
“…The component presented potent AChE inhibition activity where the result was further confirmed by docking analysis. This is in agreement with a recent study (Pereira et al, 2016) describing AChE activity of β-sitosterol which was better than oleanolic acid, ursolic acid, and corosolic acid. On the other hand, ethanol extracts of S. multicaulis exhibited a high level of inhibitory activity against BChE in contrast to AChE.…”
Section: Neuroprotectivesupporting
confidence: 93%
“…Results showed that the fraction was effective against S. aureus , B. subtilis , P. aeruginosa , and Escherichia coli . β‐sitosterol extracted from Jacaranda oxyphylla exhibited strong antimicrobial effects against Bacillus cereus , S. aureus , E. coli , Salmonella typhimurium , and Candida albicans (Pereira et al, 2016). Some of these microbes have also been used by Hamed et al (2017) to evaluate the bioactivity of β‐sitosterol purified from methanol extract of Abutilon hirtum .…”
Section: Other Pharmacological Properties Of β‐Sitosterolmentioning
confidence: 99%
“…Estado actual de las biotransformaciones con miras a la apertura de una línea de investigación en el laboratorio de fitoquímica de la Universidad Tecnológica de Pereira [Trabajo final de grado]. Universidad Tecnológica dePereira, 2016.…”
unclassified
“…The flowers of this tree are used as medicinal treatments and have been attributed with anti-inflammatory, anti-parasitic, anti-fungal, and anti-cancer properties ( Hussain et al., 2007 ), while other species in this genus have been used to treat both viral and bacterial infections ( Gachet and Schühly, 2009 ). Pereira et al. (2015) reported an inhibition halo of 96.9% and 96.6% on Bacillus cereus and S. aureus, respectively, using an ethanol extract of leaves of J. oxyphylla .…”
Section: Resultsmentioning
confidence: 99%